Pengaruh Terapi Murrotal terhadap Tingkat Nyeri dan Kecemasan pada Pasien Pasca Tindakan Radiofrequency - Muri Ambarwati; Indah Sri Wahyuningsih; Mohammad Arifin Noor (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aimed to evaluate the effect of murrotal therapy on pain and anxiety levels in patients after radiofrequency action. This study uses a quantitative approach with a pre-experimental design of one group pretest-posttest involving 50 post-radiofrequency patients at Sultan Agung Hospital Semarang. The research data were collected using the Numeric Rating Scale (NRS) instrument to assess pain levels and the Zung Self-Rating Anxiety Scale (SAS) to assess anxiety levels. Univariate analysis showed that most of the respondents were women with an average age of 44.04 years, included in the intermediate adult category. The results of bivariate analysis with the Wilcoxon Signed Rank Test showed a significant decrease in both pain and anxiety levels after being given murrative therapy, with a p-value of 0.000 for both variables. This shows that murrotal therapy is effective in providing psychological relaxation and spiritual distraction effects, so that it can reduce the intensity of pain while reducing anxiety in patients. Based on these findings, it can be concluded that murrotal therapy is a non-pharmacological intervention that is simple, safe, and easy to apply by health workers. It also has great potential as a complementary therapy that supports the management of pain and anxiety after medical procedures, especially invasive procedures such as radiofrequency. Thus, the application of murrotal therapy can be used as an additional alternative in improving the quality of nursing services in hospitals.